Deproto-metallation of N-arylated pyrroles and indoles using a mixed lithium–zinc base and regioselectivity-computed CH acidity relationship - Messaoud, Mohamed Yacine Ameur; Bentabed-Ababsa, Ghenia; Hedidi, Madani; Derdour, Aïcha; Chevallier, Floris; Halauko, Yury S.; Ivashkevich, Oleg A.; Matulis, Vadim E.; Picot, Laurent; Thiéry, Valérie; Roisnel, Thierry; Dorcet, Vincent; et al. (Beilstein Journal of Organic Chemistry, 2015)
The synthesis of N-arylated pyrroles and indoles is documented, as well as their functionalization by deprotonative metallation using the base in situ prepared from LiTMP and ZnCl2·TMEDA (1/3 equiv). With N-phenylpyrrole and -indole, the reactions were carried out in hexane containing TMEDA which regioselectively afforded the 2-iodo derivatives after subsequent iodolysis. With pyrroles and indoles bearing N-substituents such as 2-thienyl, 3-pyridyl, 4-methoxyphenyl and 4-bromophenyl, the reactions all took place on the substituent, at the position either adjacent to the heteroatom (S, N) or ortho to the heteroatom-containing substituent (OMe, Br). The CH acidities of the substrates were determined in THF solution using the DFT B3LYP method in order to rationalize the experimental results.
Keywords: CH acidity; indoles; iodolysis; mixed lithium–zinc bases; pyrroles

The Chemistry of Heterocycles - Eicher, T.; Hauptmann, S.; Speicher, A. (Wiley-VCH, 2003)

Heterocyclic Scaffolds II: Reactions and Applications of Indoles - Gribble, G. W. (Springer, 2010)

(untitled) - Gschwend, H. W.; Rodriguez, H. R. (Org. React., 2005)

(untitled) - Beak, P.; Snieckus, V. (Acc. Chem. Res., 1982)

(untitled) - Snieckus, V. (Chem. Rev., 1990)

(untitled) - Gant, T. G.; Meyers, A. I. (Tetrahedron, 1994)

Organometallics in Synthesis - Schlosser, M. (Wiley-VCH, 2002)
Chapter I.

(untitled) - Kishbaugh, T. L. S. (Top. Heterocycl. Chem., 2012)

(untitled) - Pelkey, E. T. (Top. Heterocycl. Chem., 2010)

(untitled) - Cheeseman, G. W. H.; Greenberg, S. G. (J. Organomet. Chem., 1979)

(untitled) - Faigl, F.; Schlosser, M. (Tetrahedron, 1993)

(untitled) - Shirley, D. A.; Gross, B. H.; Roussel, P. A. (J. Org. Chem., 1955)

(untitled) - Thurner, A.; Faigl, F.; Ágai, B.; Töke, L. (Synth. Commun., 1998)

(untitled) - Faigl, F.; Fogassy, K.; Thurner, A.; Töke, L. (Tetrahedron, 1997)

(untitled) - Faigl, F.; Fogassy, K.; Szántó, Z.; Lopata, A.; Töke, L. (Tetrahedron, 1998)

(untitled) - Fogassy, K.; Kovács, K.; Keserű, G. M.; Tőke, L.; Faigl, F. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Faigl, F.; Feldhoffer, B. V.; Thurner, A. (Synth. Commun., 2006)

(untitled) - Faigl, F.; Vas-Feldhoffer, B.; Kubinyi, M.; Pál, K.; Tárkányi, G.; Czugler, M. (Tetrahedron: Asymmetry, 2009)

(untitled) - Faigl, F.; Fogassy, K.; Szűcs, E.; Kovács, K.; Keserű, G. M.; Harmat, V.; Böcskei, Z.; Tőke, L. (Tetrahedron, 1999)

(untitled) - Faigl, F.; Mátravölgyi, B.; Deák, S.; Holczbauer, T.; Czugler, M.; Balázs, L.; Hermecz, I. (Tetrahedron, 2012)

(untitled) - Rataboul, F.; Zapf, A.; Jackstell, R.; Harkal, S.; Riermeier, T.; Monsees, A.; Dingerdissen, U.; Beller, M. (Chem. – Eur. J., 2004)

(untitled) - Artemova, N. V.; Chevykalova, M. N.; Luzikov, Y. N.; Nifant'ev, I. E.; Nifant'ev, E. E. (Tetrahedron, 2004)

(untitled) - Mulvey, R. E. (Organometallics, 2006)

(untitled) - Mulvey, R. E.; Mongin, F.; Uchiyama, M.; Kondo, Y. (Angew. Chem., Int. Ed., 2007)

(untitled) - Mulvey, R. E. (Acc. Chem. Res., 2009)

(untitled) - Haag, B.; Mosrin, M.; Ila, H.; Malakhov, V.; Knochel, P. (Angew. Chem., Int. Ed., 2011)

(untitled) - Mongin, F.; Uchiyama, M. (Curr. Org. Chem., 2011)

(untitled) - Mongin, F.; Harrison-Marchand, A. (Chem. Rev., 2013)

(untitled) - Mulvey, R. E. (Dalton Trans., 2013)

(untitled) - Harford, P. J.; Peel, A. J.; Chevallier, F.; Takita, R.; Mongin, F.; Uchiyama, M.; Wheatley, A. E. H. (Dalton Trans., 2014)

(untitled) - L'Helgoual'ch, J. M.; Seggio, A.; Chevallier, F.; Yonehara, M.; Jeanneau, E.; Uchiyama, M.; Mongin, F. (J. Org. Chem., 2008)

(untitled) - García-Álvarez, P.; Mulvey, R. E.; Parkinson, J. A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Seggio, A.; Lannou, M. I.; Chevallier, F.; Nobuto, D.; Uchiyama, M.; Golhen, S.; Roisnel, T.; Mongin, F. (Chem. – Eur. J., 2007)

(untitled) - Seggio, A.; Chevallier, F.; Vaultier, M.; Mongin, F. (J. Org. Chem., 2007)

(untitled) - Snégaroff, K.; Komagawa, S.; Chevallier, F.; Gros, P. C.; Golhen, S.; Roisnel, T.; Uchiyama, M.; Mongin, F. (Chem. – Eur. J., 2010)

(untitled) - Snégaroff, K.; Nguyen, T. T.; Marquise, N.; Halauko, Y. S.; Harford, P. J.; Roisnel, T.; Matulis, V. E.; Ivashkevich, O. A.; Chevallier, F.; Wheatley, A. E. H.; Gros, P. C.; Mongin, F. (Chem. – Eur. J., 2011)

(untitled) - Chevallier, F.; Halauko, Y. S.; Pecceu, C.; Nassar, I. F.; Dam, T. U.; Roisnel, T.; Matulis, V. E.; Ivashkevich, O. A.; Mongin, F. (Org. Biomol. Chem., 2011)

(untitled) - Chevallier, F.; Blin, T.; Nagaradja, E.; Lassagne, F.; Roisnel, T.; Halauko, Y. S.; Matulis, V. E.; Ivashkevich, O. A.; Mongin, F. (Org. Biomol. Chem., 2012)

(untitled) - Kadiyala, R. R.; Tilly, D.; Nagaradja, E.; Roisnel, T.; Matulis, V. E.; Ivashkevich, O. A.; Halauko, Y. S.; Chevallier, F.; Gros, P. C.; Mongin, F. (Chem. – Eur. J., 2013)

(untitled) - Nagaradja, E.; Chevallier, F.; Roisnel, T.; Dorcet, V.; Halauko, Y. S.; Ivashkevich, O. A.; Matulis, V. E.; Mongin, F. (Org. Biomol. Chem., 2014)

(untitled) - Marquise, N.; Bretel, G.; Lassagne, F.; Chevallier, F.; Roisnel, T.; Dorcet, V.; Halauko, Y. S.; Ivashkevich, O. A.; Matulis, V. E.; Gros, P. C.; Mongin, F. (RSC Adv., 2014)

(untitled) - Matulis, V. E.; Halauko, Y. S.; Ivashkevich, O. A.; Gaponik, P. N. (J. Mol. Struct.: THEOCHEM, 2009)

(untitled) - Halauko, Y. S.; Matulis, V. E.; Ivashkevich, O. A.; Grigoriev, Y. V.; Gaponik, P. N. (Tetrahedron, 2010)

(untitled) - Zhu, R.; Xing, L.; Wang, X.; Cheng, C.; Su, D.; Hu, Y. (Adv. Synth. Catal., 2008)

(untitled) - Antilla, J. C.; Baskin, J. M.; Barder, T. E.; Buchwald, S. L. (J. Org. Chem., 2004)

(untitled) - Huisgen, R.; Mack, W.; Herbig, K.; Ott, N.; Anneser, E. (Chem. Ber., 1960)

(untitled) - Teo, Y.-C.; Yong, F.-F.; Sim, S. (Tetrahedron, 2013)

(untitled) - Bordwell, F. G. (Pure Appl. Chem., 1977)

(untitled) - Del Valle, J. C.; De Paz, J. L. G. (J. Mol. Struct.: THEOCHEM, 1992)

(untitled) - Vianello, R.; Maksić, Z. B. (Mol. Phys., 2005)

(untitled) - Fraser, R. R.; Mansour, T. S.; Savard, S. (Can. J. Chem., 1985)

(untitled) - Shen, K.; Fu, Y.; Li, J.-N.; Liu, L.; Guo, Q.-X. (Tetrahedron, 2007)

(untitled) - Mongin, F.; Schlosser, M. (Tetrahedron Lett., 1997)

(untitled) - Schlosser, M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Gottlieb, H. E.; Kotlyar, V.; Nudelman, A. (J. Org. Chem., 1997)

(untitled) - Altomare, A.; Burla, M. C.; Camalli, M.; Cascarano, G. L.; Giacovazzo, C.; Guagliardi, A.; Moliterni, A. G. G.; Polidori, G.; Spagna, R. (J. Appl. Crystallogr., 1999)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A, 2008)

(untitled) - Farrugia, L. J. (J. Appl. Crystallogr., 1999)

(untitled) - Farrugia, L. J. (J. Appl. Crystallogr., 1997)

(untitled) - Hedidi, M.; Bentabed-Ababsa, G.; Derdour, A.; Roisnel, T.; Dorcet, V.; Chevallier, F.; Picot, L.; Thiéry, V.; Mongin, F. (Bioorg. Med. Chem., 2014)

Gaussian 03, Revision C.01 (Gaussian, Inc., 2003)